Linguistic Addition Errors in Indonesian Academic Writing: A Syntactic Analysis of Reduplication, Conjunctions, and Prepositions - Arju Susanto; A. Muh. Ayyub Ht; M. Nur Iman; Nur Qadri Malabbi (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates addition errors in Indonesian academic writing, particularly unnecessary linguistic elements that create ineffective sentence constructions. The research aims to identify and analyze patterns of addition errors found in students’ academic texts. This study employed a qualitative descriptive method using documentation and note-taking techniques. The data consisted of 24 ungrammatical sentences collected from Indonesian academic writings. The findings revealed eight dominant patterns of addition errors: reduplication with banyak, banyaknya, beberapa, jumlah, and seluruh; subordinate clause construction jika…, maka…; addition of the preposition pada; and addition of the conjunction yang. The results indicate that students frequently produce redundant grammatical structures by combining plural markers with reduplication, inserting unnecessary conjunctions, and adding excessive prepositions. These errors reduce sentence effectiveness, clarity, and conciseness in academic writing. The study concludes that addition errors are mainly influenced by spoken language interference, overgeneralization of grammatical rules, and limited understanding of formal Indonesian syntax. Therefore, academic writing instruction should emphasize effective sentence construction, grammatical economy, and editing strategies to minimize unnecessary linguistic additions in scholarly writing.